Senior Public Managers: A Novel Dataset on Members of the Chilean Civil Service [Altos Directivos Páblicos: Un Nuevo Conjunto de Datos de Miembros del Servicio Civil Chileno] - Gonzalez-Bustamante, B (Universidad De Valparaiso, 2020)
This paper presents a novel dataset of senior public managers in Chile in 2009-2017. This methodological study focuses on demonstrating how data mining and machine learning can be useful for the creation of the dataset and its potential applications. We explain how we created and validated the dataset before going in to present some descriptive applications and nonparametric survival estimates with Kaplan-Meier curves. We hope that this dataset will serve as a relevant resource for gaining a deeper understanding of the Chilean civil service and making different comparisons through which to expand this research line on political and government personnel. © 2020 Universidad De Valparaiso. All Rights Reserved.